Prognostic Role of the Neutrophil-to-Lymphocyte Ratio in Intracerebral Hemorrhage: A Systematic Review and Meta-Analysis - Shi, Min; Li, Xiao-feng; Zhang, Ting-bao; Tang, Qing-wen; Peng, Mian; Zhao, Wen-yuan (Frontiers in Neuroscience, 2022)
The ratio of neutrophils to lymphocytes (NLR) plays an important role in the progression of intracerebral hemorrhage (ICH). An increasing number of studies have reported that a high NLR is correlated with poor clinical outcomes among patients with ICH. Here, we conducted a systematic review and meta-analysis to evaluate the prognostic value of NLR in the setting of ICH. We performed a comprehensive search of electronic literature databases to identify all relevant studies evaluating the prognostic role of NLR in patients with ICH. Two researchers independently screened the studies and extracted relevant data. We extracted, pooled, and weighted odds ratio (OR) and 95% confidence interval (CI) values using a generic inverse-variance method, and then evaluated the heterogeneity among studies using Q test and I2 statistic. Finally, we selected a total of 26 studies including 7,317 patients for the current study. Overall, our results indicated that a high NLR was significantly associated with a poor outcome (OR, 1.32; 95% CI, 1.19–1.46; P < .00001), mortality (OR, 1.05; 95% CI, 1.01–1.09; P = .02), and neurological deterioration (OR, 1.65; 95% CI, 1.08–2.52; P = .02). We did not observe a significant association between NLR and hematoma expansion (OR, 1.04; 95% CI, 0.99–1.08; P = .09). Our study indicated that a high NLR is significantly associated with poor clinical outcomes in patients with ICH. As NLR is a simple and easily available biomarker, future studies should focus on exploring its application in the prognostic evaluation of patients with ICH.